Energy Flow Through Marine Ecosystems: Confronting Transfer Efficiency. (January 2021) - Eddy, Tyler D.; Bernhardt, Joey R.; Blanchard, Julia L.; Cheung, William W.L.; Colléter, Mathieu; du Pontavice, Hubert; Fulton, Elizabeth A.; Gascuel, Didier; Kearney, Kelly A.; Petrik, Colleen M.; Roy, Tilla; Rykaczewski, Ryan R.; et al.
Abstract : Transfer efficiency is the proportion of energy passed between nodes in food webs. It is an emergent, unitless property that is difficult to measure, and responds dynamically to environmental and ecosystem changes. Because the consequences of changes in transfer efficiency compound through ecosystems, slight variations can have large effects on food availability for top predators. Here, we review the processes controlling transfer efficiency, approaches to estimate it, and known variations across ocean biomes. Both process-level analysis and observed macroscale variations suggest that ecosystem-scale transfer efficiency is highly variable, impacted by fishing, and will decline with climate change. It is important that we more fully resolve the processes controlling transfer efficiency in models to effectively anticipate changes in marine ecosystems and fisheries resources. Highlights: Transfer efficiency is a key parameter describing ecosystem structure and function and is used to estimate fisheries production; however, it is also one of the most uncertain parameters. Questions remain about how habitats, food resources, fishing pressure, spatiotemporal scales, as well as temperature, primary production, and other climate drivers impact transfer efficiency. Direct measurements of transfer efficiency are difficult, but observations of marine population abundances, diets, productivity, stable isotope analysis, and models integrating these constraints can provide transfer efficiency estimates. Recent estimates suggest that transfer efficiency is more variable than previously thought, compounding uncertainties in marine ecosystem predictions and projections. Increased understanding of factors contributing to variation in transfer efficiency will improve projections of fishing and climate change impacts on marine ecosystems.